2020
DOI: 10.1111/joor.13056
|View full text |Cite
|
Sign up to set email alerts
|

When to install the endodontic post? First visit with root canal filling versus a separate second visit for post‐restoration: A randomized controlled trial

Abstract: Background The vibrations created by post‐space preparation during the first visit for endodontic treatment could have a significant effect on the intensity of post‐operative pain than that association with post‐space preparation at the second appointment. Objective The aim of this study was to evaluate the effect of vibrations generated during post‐installation, on post‐operative pain in endodontically treated teeth. Methods One hundred patients with asymptomatic teeth requiring primary root canal treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…An electronic pain rating scale program with a vertical visual analog scale (VAS) was used after the first visit for both groups to evaluate post-operative pain by an RCT (Table 7 ) [ 11 ]. Results presented no post-operative pain in patients with delayed post cementation, in contrast, there was significantly higher post-operative pain in immediate post installation on days 1, 2 and 3 and 1 week after the first visit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An electronic pain rating scale program with a vertical visual analog scale (VAS) was used after the first visit for both groups to evaluate post-operative pain by an RCT (Table 7 ) [ 11 ]. Results presented no post-operative pain in patients with delayed post cementation, in contrast, there was significantly higher post-operative pain in immediate post installation on days 1, 2 and 3 and 1 week after the first visit.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized controlled trial evaluated the post-operative pain of PSP and showed the vibrations generated during post-installation by a low-speed handpiece with dedicated fiber post drills from the post kit in the same visit of root canal filling might increase the post-operative pain. Therefore, the cumulative effect of root canal treatment and post installation in the first visit might increase the intensity of pain [ 11 ]. Although delayed PSP was recommended, more studies are necessary to thoroughly investigate the effects of the timing of PSP on post-operative pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors play important roles in endodontic pain, such as host-dependent, chemical, or mechanical injury, or bacterial infection [2]. In particular, apical extrusion of infected debris and mechanical vibration and/or noise created by different handpieces during root canal instrumentation have also been shown to affect postoperative pain [3][4][5]. Several studies have investigated the effect of procedural methodology on postoperative pain, such as the number of visits [6], endodontic les with different kinematics [7,8], and irrigation [9] or lling protocols [10], proving that these factors affect postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are con icting results among these studies that may be associated with the subjectivity of the data on postoperative pain [7,11]. It has been recognized that during data collection in the studies mentioned above, some studies demand the presence of patients in the clinic for all follow-up periods [4,7], whereas others simply schedule a telephonic conversation with patients for pain intensity evaluations [8,9].…”
Section: Introductionmentioning
confidence: 99%